Effect of Posterior Corneal Surgically Induced Astigmatism on Toric Intraocular Lens Power Calculations - Stewart S; Yeo TK; Moutari S; McNeely RN; Moore JE (Clinical Ophthalmology)
Stephen Stewart,1– 3 Tun Kuan Yeo,3 Salissou Moutari,4 Richard N McNeely,1 Jonathan E Moore1 1Cathedral Eye Clinic, Belfast, UK; 2Centre for Public Health, Queen’s University Belfast, Belfast, UK; 3National Health Group Eye Institute, Tan Tock Seng Hospital, Singapore, Singapore; 4School of Mathematics and Physics, Queen’s University Belfast, Belfast, UKCorrespondence: Stephen Stewart, Cathedral Eye Clinic, 89-91 Academy Street, Belfast, BT1 2LS, UK, Email stephen.stewart@doctors.org.ukBackground: To determine whether accounting for posterior corneal surgically induced astigmatism (SIA) would improve toric intraocular lens power calculation prediction error.Methods: A total of 189 eyes of 148 patients undergoing routine cataract surgery were included in the study. Standard and posterior keratometry were measured pre- and postoperatively. Centroid SIA with standard keratometry and posterior keratometry were calculated separately. Prediction errors for postoperative refractive astigmatism at 4 weeks postoperatively were compared for Barrett Toric with predicted posterior corneal astigmatism (PPCA); Barrett Toric with preoperative measured posterior corneal astigmatism (MPCA); Barrett Toric with postoperative MPCA, which accounts for posterior corneal SIA.Results: There was a significant increase in PCA magnitude postoperatively (p < 0.001), although a change of > 0.3D occurred in only 3% of eyes. There was a postoperative rotation in the steep meridian of > 10° in 32% of eyes. The Barrett Toric formula with PPCA yielded a significantly smaller refractive astigmatism prediction error compared to when a postoperative MPCA value was used (p < 0.01). Postoperative MPCA had a lower proportion of eyes within 0.50, 0.75 and 1.00D of predicted refractive astigmatism than PPCA or preoperative MPCA, although this was not statistically significant.Conclusion: This study demonstrated postoperative changes in posterior corneal astigmatism magnitude and the orientation of the steep meridian. However, accounting for posterior keratometric SIA in the Barrett Toric formula does not improve refractive astigmatism prediction accuracy.Keywords: cataract, posterior corneal astigmatism, Toric IOL power calculations